(3bhGYO GdYbGFOs - (3GdWhSj, CHh LYaQ, fUjQ GdOjf, eMeO Hf eMeO Hf GdMSf, J (B672 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B.. (3GdHGH GdKGfj aj PcQ UaGJ Gddg hgj JfbSe Edi KHhJjI hZjQ KHhJjI , Ce GdKHhJjI aefgG Cfg JYGdi bGOQ hGdbGOQ GdPj jUM efg Cf jaYd hEPG aYd aYd HGNJjGQ hEQGOI (B...s
(3BNQgG (B:s
.. (3bGdhG HeKd Pdc CYfj HhLhH MUhd GdbYd eY GdbOQI hGdEQGO(B.. (3hGdeYJRdI bGdhG Cfg jQjO eG jaYdg hCeG Ge jaYdg GdYHO agh jQjO WGYJg hdG jQjO eYUjJg hgPg GdEQGOI (B.. (3aj GdeYfi JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, ddRQcdj (B7/ 30s
(3GdPQjYI (B17\985s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds